2020
DOI: 10.1098/rstb.2019.0638
|View full text |Cite
|
Sign up to set email alerts
|

The critical importance of experimentation in biomarker-based trophic ecology

Abstract: Fatty acids are commonly used as biomarkers for making inferences about trophic relationships in aquatic and soil food webs. However, researchers are often unaware of the physiological constraints within organisms on the trophic transfer and modification of dietary biomarkers in consumers. Fatty acids are bioactive molecules, which have diverse structures and functions that both complicate and enhance their value as trophic tracers. For instance, consumers may synthesize confounding non-dietary sourced markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…This assumption likely did not hold in all cases, especially for short-term studies with adult organisms, and contributes to some of the scatter we observed in the regression analysis. In very few cases do we know the true tissue-turnover time for FA, which is an important area for future research [31].…”
Section: Methodsmentioning
confidence: 99%
“…This assumption likely did not hold in all cases, especially for short-term studies with adult organisms, and contributes to some of the scatter we observed in the regression analysis. In very few cases do we know the true tissue-turnover time for FA, which is an important area for future research [31].…”
Section: Methodsmentioning
confidence: 99%
“…However, the modeling attempt of Sawyer et al ( 2016 ), estimated that the dominant uptake pathway for EPA in Yellow perch [ Perca flavescens (Mitchill 1814)], a close relative to the Eurasian perch, would be ingestion, but up to 87% of the Yellow perch’s DHA would be obtained via internal conversion. Unfortunately, we cannot estimate transformation rates from our data, and further experimental studies are needed to determine the specific physiological processes involved to regulate HUFA levels in natural perch feeding types, but more generally also on the uptake and transfer of trophic biomarkers in organisms across the whole animal kingdom (Galloway et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this view ignores the ability of consumer to modify fatty acids via internal transformation, such as selective retention or mobilization, and bioconversion, by elongating and/or desaturating shorter chained fatty acid precursors into HUFAs (Bell et al 2009 ; Twining et al 2016 ). To understand the ability and the extent of consumers to modify the dietary fatty acids is of critical importance for quantitative and qualitative approaches of fatty acids in ecological research (Galloway et al 2020 ). The major pathways for the conversion of HUFAs (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, metabolic profiles can be explored to (a) understand the relationships between physiological responses and environmental factors and (b) to identify specific biomarkers (e.g., naturally occurring molecules) of distinct environmental responses, and (c) monitor the uptake of trophic biomarkers in individual organisms. These biomarkers can be identified and evaluated on the scale of entire populations or ecosystems (Galloway & Budge, 2020).…”
Section: Introductionmentioning
confidence: 99%